Determinantes de las capacidades de innovación en el sector biotecnológico en México - Mario A. Morales Sánchez; Héctor Eduardo Díaz Rodríguez (Investigación Económica, 2019)
– Technological innovation is a process linked to the generation of knowledge and the way in which companies learn and develop innovations. It depends on the particular context in which firms operate. As the potential of biotechnology has to support a wave of growth in other sectors, this study focuses on identifying and measuring innovation capabilities, as well as the determinants of such capabilities in the Mexican biotechnology companies. The results show that the existence of networks (financial, knowledge, collaboration, among others) that allow generating both an adequate flow of knowledge and the capacities of companies to take advantage of such knowledge, are determining factors of the innovative dynamism.
Keywords: L69; O31; O32; 330; Biotechnology; innovation; knowledge networks